[PP.16.16] THE FIRST RISK SCORING SYSTEM FOR SUDDEN DEATH PREDICTION IN PRIMARY PREVENTION PATIENTS. (September 2016) - Le, H.; Subtil, F.; Cerou, M.; Fall, M.; Al Gobari, M.; Marchant, I.; Kassai, B.; Chevalier, P.; Gueyffier, F.
Abstract : Objective: Sudden death (SD) defined as a death within 1 h from the onset of symptom, is a common cardiovascular accident, even more frequent than fatal myocardial infarction (FMI). Up to now, DUKE is the only SD risk predictor and designed specifically for patients with angiographic coronary artery diseases. We built here the first sudden death risk scoring system for primary prevention, developed in patients with hypertension and type 2 diabetes. In addition, we analysed and compared the risk factors of SD and of FMI, the two close associated cardiovascular accidents. Design and method: We used the Cox model to build this risk score on R (version 3.2.2) based on 30 560 individual data from seven randomized controlled trials (six of INDANA database in hypertension & one in type 2 diabetes Diahhycab). The risk equation then was translated to scoring system to facilitate the clinical use. Comparison of risk factors between SD and FMI was based on 15 279 individual data from the same RCTs but only in placebo group (to avoid treatment bias, since antihypertensive/antidiabetic drugs may decrease the FMI risk). Results: There was no treatment effect and no interaction between treatment and other covariates on the risk of SD. This allowed us to develop the model on both treatment/placebo groups. We identified seven risk factors of SD: age, sex (male), smoking, cholesterolemia, systolic blood pressure, baseline of type 2 diabetes and history of myocardial infarction. The discrimination performance of the tool was fair, with area under the receiver operating characteristic curve (AUC) about 70%. FMI shared the same risk factors of SD, except cholesterolemia that did not reach statistical significance. Conclusions: Our work provides the first risk score for SD prediction in primary prevention patients. This risk score, in particular in hypertension and type 2 diabetes could help stratify patients in order to optimize preventive therapeutic strategies in primary prevention. Further research on SD is required to better prevent this highly frequent and relatively ignored form of death.